Prognostic impact of dynamic changes of type I melanoma antigen gene proteins CT7 (MAGE-C1/CT7) transcripts in multiple myeloma - Xuelin Dou; Fengrong Wang; Huan Chen; Yao Chen; Lei Wen; Yang Liu; Guorui Ruan; Xiaosu Zhao; Xiaojun Huang; Robert Peter Gale; Jin Lu; Jin Lu (Frontiers in Medicine)
Type I melanoma antigen gene proteins CT7 (MAGE-C1/CT7), a cancer-testis (CT) gene, correlated with clinical parameters at diagnosis of multiple myeloma (MM). We first analyzed single-cell ribonucleic acid sequencing data from public databases to evaluate the expression of MAGE-C1/CT7 in MM patients and showed that MAGE-C1/CT7 is highly and specifically expressed in the MM cells. We then interrogated data from 216 consecutive cases with MAGE-C1/CT7 transcripts by quantitative real-time polymerase chain reaction longitudinally monitored in our center. The positive rate of MAGE-C1/CT7 at baseline was 87.3%, with a median level of 4.46% (0.01–939.5). In univariate Cox regression analysis, peri-ASCT MAGE-C1/CT7 status showed better discriminatory ability in PFS and survival than peri-ASCT multi-parameter flow-cytometry status assessed by flow cytometry. In multivariate analysis, patients who were MAGE-C1/CT7-negative pre-transplant and posttransplant had significantly better PFS than those who were positive in both determinations (HR = 0.33, 95% CI: 0.14, 0.80, p = 0.01). In 69 patients with informative samples, we found a 2-log decrease in MAGE-C1/CT7 transcript concentration after the second induction cycle correlated with achieving negative MAGE-C1/CT7-test results both pre-transplant and posttransplant (OR = 6.08, 95% CI: 1.78, 20.74, p = 0.004). Our data showed the predictive value of peri-ASCT frontline treatment. A 2-log decrease of MAGE-C1/CT7 post-induction cycle 2 compared to baseline correlated with a negative peri-ASCT MAGE-C1/CT7 status, providing an earlier prognostic marker of treatment response.